Nanocomposites Based on PLLA and Multi Walled Carbon Nanotubes Support the Myogenic Differentiation of Murine Myoblast Cell Line. (1st July 2013) - Montesano, Simona; Lizundia, Erlantz; D'Angelo, Francesco; Fortunati, Elena; Mattioli, Samantha; Morena, Francesco; Bicchi, Ilaria; Naro, Fabio; Sampaolesi, Maurilio; Sarasua, Josè Ramon; Kenny, Josè Maria; Orlacchio, Aldo; et al.
Abstract : We explored the effect of poly(L-lactic acid) (PLLA) containing various percentages (0.1, 0.5, 1, and 3 wt.%) of multi walled carbon nanotubes (MWCNTs) on the myogenic differentiation of C2C12 murine myoblast progenitor cells. We showed that all PLLA/MWCNTs nanocomposite materials support the myotubes formation more efficiently than neat PLLA as indicated by the high expression of the most significant myogenic markers: MyoD, Myosin Heavy Chain, dimension of myofibres, and fusion myogenic index. Interestingly, we note that both MyoD and myogenic fusion index levels were in the order 0.1 MWCNTs = 0.5 MWCNTs > 1 MWCNTs > 3 MWCNTs > neat PLLA, suggesting that the amount of MWCNTs influenced the cell differentiation.